Disciplinary differences in altmetrics for social sciences - Htoo, Tint Hla Hla (2017)
Purpose - The purpose of this paper is to contribute to the understanding of altmetrics in different disciplines of Social Science, first, by investigating the current richness and future potential of altmetrics in the selected social science disciplines and then, by evaluating the validity of altmetrics as indicators of research impact in each discipline through correlation analysis.